Perceptions about Internationalization Barriers in the Creative Economy: a Multiple-Case Study with Brazilian SMEs - Soares, Fernando Januário Lopes; Ferreira da Silva, Jorge (Internext, 2022)
Objective: to explore perceptions that stakeholders of Brazilian firms from the Creative Economy have regarding internationalization barriers. Method: a multiple-case study was carried out involving three small- and medium-sized Brazilian enterprises (SMEs), all of them producers and experienced exporters of creative goods. Main findings: internal barriers, mainly those functional- and price-related, are perceived as the most important, while product-related barriers seem to be irrelevant. Among external barriers, economic and governmental constraints seem to stand out, which indicates the need for some regulatory and export incentive improvement. Relevance/ originality: while exports of creative goods from emerging economies have grown since the beginning of this century and even surpassed those from developed economies, Brazil has gone in the opposite direction, reducing its exports of this kind of goods. This suggests the existence of relevant barriers to the internationalization of local firms belonging to the Creative Economy. This study adds to the literature about export barriers, traditionally focused on large manufacturers from developed economies. Theoretical/ methodological contributions: the identified preponderance of internal barriers to internationalization, mainly due to the scarcity of human and financial resources, also makes it harder for the firms to deal with external barriers imposed by governments and competitors. On the other hand, low product-related and socioeconomic barriers suggest that creative products are most valued precisely by their originality and differentiation.